2021
DOI: 10.1159/000512292
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience of Endoscopic Submucosal Dissection for Ulcerative Colitis-Associated Neoplasia

Abstract: Introduction: Patients with ulcerative colitis (UC) have an increased risk of colorectal cancer. Some studies have recently investigated endoscopic resection of UC-associated neoplasia (UCAN), but the indications for endoscopic resection of UCAN remain controversial. This study sought to clarify the problems encountered in endoscopic submucosal dissection (ESD) for UCAN. Methods: Seventeen lesions in 12 patients with UCAN (UCAN group) and 913 epithelial lesions in 824 control patients without UC (non-UC group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…However, factors that affected the resection rates were different among the studies. In our meta-analysis, the reasons for R0 resection and noncurative resection were severe submucosal fibrosis [ 14 , 16 , 18 , 19 ], deep submucosal invasion of cancer [ 14 16 ], and positive horizontal margin [ 15 , 21 ]. The different reasons for non R0 resection among these studies might be the source of heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, factors that affected the resection rates were different among the studies. In our meta-analysis, the reasons for R0 resection and noncurative resection were severe submucosal fibrosis [ 14 , 16 , 18 , 19 ], deep submucosal invasion of cancer [ 14 16 ], and positive horizontal margin [ 15 , 21 ]. The different reasons for non R0 resection among these studies might be the source of heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Of these articles, 13 studies were selected for further full-text evaluation after a review of the titles and abstracts. Of the 13 records, 8 studies fulfilled the criteria for inclusion in a quantitative synthesis (meta-analysis) [14][15][16][17][18][19][20][21].…”
Section: Study Selectionmentioning
confidence: 99%
“…Second, the differentiation of sporadic neoplasia from UCAN is also challenging: even the histological definition has not been confirmed. However, the treatment strategy is an important issue: aggressive endoscopic treatment is gaining acceptance as a diagnostic option for sporadic neoplasms but is still controversial for colitis‐associated neoplasia 42,54–58 …”
Section: Discussionmentioning
confidence: 99%
“…No research to date has focused on optical diagnosis of the horizontal extent of lesions. Matsui et al 57 . evaluated the outcomes of endoscopic submucosal dissection and found that 29% (5/17) of cases had a positive horizonal margin, mainly due to an undetected demarcation line of dysplasia around the superficial elevated lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of ESD is total excision biopsy to evaluate the lesion. Compared to non-UC patients, ESD in UC is associated with lower rate of Ro resection (71% vs. 93%) with lower probability of negative horizontal margin [50]. Hence the demarcation line should be ascertained.…”
Section: Endoscopic Submucosal Dissection (Esd)mentioning
confidence: 99%